2017
DOI: 10.1111/nph.14603
|View full text |Cite
|
Sign up to set email alerts
|

Experimental soil warming shifts the fungal community composition at the alpine treeline

Abstract: Increased CO emissions and global warming may alter the composition of fungal communities through the removal of temperature limitation in the plant-soil system, faster nitrogen (N) cycling and changes in the carbon (C) allocation of host plants to the rhizosphere. At a Swiss treeline featuring Larix decidua and Pinus uncinata, the effects of multiple years of CO enrichment and experimental soil warming on the fungal community composition in the organic horizons were analysed using 454-pyrosequencing of ITS2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 96 publications
3
44
1
Order By: Relevance
“…Mycorrhizal activity has frequently been observed to decline with N fertilization (Högberg et al, ; Nilsson & Wallander, ; Wallander & Nylund, ). Further, in an experiment near our study site where soil warming led to greater N availability, Solly, Lindahl et al () observed a shift in the fungal community composition towards more nitrophilic species.…”
Section: Discussionmentioning
confidence: 51%
“…Mycorrhizal activity has frequently been observed to decline with N fertilization (Högberg et al, ; Nilsson & Wallander, ; Wallander & Nylund, ). Further, in an experiment near our study site where soil warming led to greater N availability, Solly, Lindahl et al () observed a shift in the fungal community composition towards more nitrophilic species.…”
Section: Discussionmentioning
confidence: 51%
“…Overall, soil moisture seemed to be more important than temperature in explaining variation in fungal community composition in this ecosystem. By contrast, studies of subarctic and alpine tree line ecosystems have reported that warming may cause important fungal community shifts and changes in soil fungal biomass, because higher temperatures may stimulate nutrient cycling and plant production (Clemmensen et al ., ; Solly et al ., ). Here, soil fungal biomass was lower during summer than during autumn and spring, supporting previous reports from other Mediterranean forest ecosystems (Iotti et al ., ; Castaño et al ., ; Queralt et al ., ) and potentially reflecting differences between Mediterranean and boreal forest ecosystems.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that changes in climatic conditions may affect soil fungal communities, directly or indirectly (Fernandez et al ., ; Hartmann et al ., ; Solly et al ., ). Mycorrhizal species have shown contrasting responses to changes in climate, and responses are modulated by nutrient availability (Clemmensen et al ., ; Solly et al ., ) and host tree responses (Fernandez et al ., ; Hartmann et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations